Faktor-Faktor yang Mempengaruhi Nilai Perusahaan pada Perusahaan Sub-Sektor Farmasi: Factors Affecting Company Value in Pharmaceutical Sub-Sector Companies - Apriani, Dinda; Lupikawaty, Marieska; Purnamasari, Keti (Jurnal Aplikasi Manajemen dan Bisnis, 2024)
The purpose of this study is to examine how firm value is influenced by liquidity, leverage, firm size and profitability partially and simultaneously. Purposive sampling was used to select nine pharmaceutical subsector companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2022. The analysis uses panel data regression. The results show that simultaneously liquidity measured using current ratio, leverage with debt to asset ratio, firm size using natural logarithm (total assets) and profitability measured through return on assets affect firm value measured by price book value. Profitability partially has an impact on firm value but liquidity, leverage and firm size have no effect. This research suggests that companies and investors should re-evaluate other factors that impact firm value. Morever, for future researchers, they can add various other factors and develop this research further.